Marketing Mix (4P) and Consumer Perception: Evidence from CNI Indonesia - Tiara Lutfiyah Andini; Ilsya Hayadi (JWM (JURNAL WAWASAN MANAJEMEN), 2026)
This study aims to analyze the effect of marketing mix elements (product, price, place, and promotion) on the perceptions of PT Citra Nusa Insan Cemerlang (CNI) consumers in Indonesia. The research method used a quantitative approach involving 210 respondents who had used CNI products, and the data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results show that all marketing mix variables have a positive and significant effect on consumer perceptions (p < 0.05), with an R² value of 0.557, which means that the model can explain 55.7% of the variation in consumer perceptions. These findings confirm that the integrated application of the 4P strategy can strengthen positive consumer perceptions. Practically, this study provides input for CNI and similar companies in designing more effective marketing strategies, as well as filling the gap in studies related to the transition from MLM systems to marketing mix in Indonesia.